Characteristics and mechanism of the particle migration subject to the shear flow of concrete flow under pressure - Xie, Xiangyu; Liu, Xuemei; Ding, Faxing; Zhang, Lihai (Journal of Building Engineering, 2023)
The concrete flow under pressure highly depends on the formation of a lubrication layer between the concrete mass and the pipe wall. Though it is widely believed that particle migration under shear flow influences the formation of this layer, the exact mechanism remains unclear. Therefore, a fully coupled computational fluid dynamic - discrete element method (CFD-DEM) model is developed to investigate the dynamic behaviour of the aggregates within the pipe flow and validated via computed tomography (CT) study and aggregate phase segmentation. The characteristics and influencing factors of the particle migration process is examined by the validated model. The sub-spheres method is employed to accurately model the aggregate shapes in the model. It reveals that the uneven distribution of particle collision frequency contributes to radial particle migration and the subsequent formation of the lubrication layer. The extent of particle migration is found to depend on the pipe size, but independent on the flow rate. The methodology and findings of this paper will also be useful for three dimensional (3D) printing concrete. •A fully coupled CFD-DEM model is established to investigate the dynamic behavior of the aggregates during concrete flow and validated via computerd tomgraphy (CT) study.•The aggregate distribution after pumping is quantified by Computed Tomography.•A sub-spheres method is adopted to accurately model the aggregate shapes in the model.•The inhomogeneous distribution of particle collision induces particle migration.•The lubrication layer changes with pipe geometry, rather than flow rate.